KVINDEFÆNGSEL – ET RELEVANT ALTERNATIV? EN DESKRIPTIVT BASERET FREMSTILLING - Mathiassen, Charlotte (Psyke & Logos, 2015)
Compared to male prisoners, imprisoned women are a minority. 4-6 % of the entire prison population are women. Women primarily serve their sentences in four prisons together with men. Thereby, men and women in these prisons do not serve segregated. As no research based knowledge existed of female prisoners and their experiences in gender mixed facilities, the Danish correctional service ordered a scientific report on women prisoners’ everyday life in Danish prisons. None of the participating women had ever served time in a women’s prison and several of them were reluctant about the idea. The article analyses the different reasons for their reservations.